Effective Fiscal-Monetary Interactions in Severe Recessions - Chen, Jiaqian (IMF Working Papers; Working Paper ;, 2022)
The COVID-19 pandemic and the subsequent need for policy support have called the traditional separation between fiscal and monetary policies into question. Based on simulations of an open economy DSGE model calibrated to emerging and advance economies and case study evidence, the analysis shows when constraints are binding a more integrated approach of looking at policies can lead to a better policy mix and ultimately better macroeconomic outcomes under certain circumstances. Nonetheless, such an approach entails risks, necessitating a clear assessment of each country's circumstances as well as safeguards to protect the credibility of the existing institutional framework.